TEACHER’S INTERACTIONAL MODIFICATIONS AND THE STUDENTS’ RESPONSES IN INTERMEDIATE ENGLISH CLASSROOM - Gisela Elshadelin; Josefa J. Mardijono (Institute of Research and Community Outreach - Petra Christian University, 2017)
This study is about the teacher’s interactional modifications in teaching the intermediate students in an English Course in Surabaya. The three objectives of this study are to find out the types of the teacher’s interactional modifications, the students’ responses toward the teacher’s interactional modifications, and the contribution of the interactional modifications for the students’ learning. The subject of the data is an English teacher and fourteen students. Moreover, the theory applied was a theory of the interactional modifications from William, Inscoe, and Tasker (2014). The findings revealed that the teacher used five types of interactional modifications namely confirmation check, clarification request, comprehension check, repetition, and reformulation. While for the students’ responses, it showed that the students gave correct responses, incorrect responses, and no responses. Furthermore, it also revealed that interactional modifications gave four contributions; making the meaning more comprehensible for the learners, improving the learners’ language, minimizing the misunderstanding between the teacher and the learners, and ensuring that the learners were following. Finally, the writer concluded that the interactional modifications help the learners to learning the language